BUDIDAYA SHELL BACKDOOR DI PANTAI BOLOK KUPANG - NUSA TENGGARA TIMUR - Nahak, Priska Gardeni; Trisnoyuwono, Diarto (P3M- Politeknik Negeri Kupang, 2016)
NTT Province as one of the provinces in Indonesia has many islands, with the main livelihood of the people were farming, gardening and seaweed farmers. One of the flagship products of seafood NTT was seaweed. Kupang district is one of the producers of seaweed in the province, but the availability of area for those matter until now not able to meet the maximum target of dry seaweed. Additionally dried seaweed produced has poor quality because it still contains a lot of impurities, thus affecting the selling price, which would certainly have an impact on the income and welfare of the farmers. It is because the technique that applied to both the cultivation technique and drying techniques were still very traditional. One of the technologies offered to overcome those problems was 'Dryer Box Technology'. This technology were expected especially to minimize the amount of seaweed ready for harvest were always broken and lost in the rainy season, due to lack of seaweed dryers facilities. In addition by these technology were also expected to get more cleaner dried seaweed because it is not contaminated with dirt when drying, so as to improve the quality of the dried seaweed. This quality improvement, also will increase the selling price of which would increase the income and welfare of farmers seaweed, as well as increasing the amount of seaweed production in NTT Province. The dryer box technology has a dimension 0.8 m lenght; 0.66 m width; and 1.5 m height. so that for once the drying process, 50 kg of wet grass only requires about 0.53 m² of area, while using traditional drying methods requires 10m² ± s / d 15 m² of area depending on the number of wet grass. Besides shorter drying time is for 50 kg of wet grass, it takes only about ± 0.75 hours. Whereas with traditional systems, drying time takes an average of 3-4 days. This will increase the productivity of dry seaweed, which can increase the production quantity of dried seaweed ready though in NTT Province.